Reseña de Fernández Pérez, M. (1999), Introducción a la Lingüística, Barcelona, Ariel. - Inmaculada Penadés Martínez (Pragmalingüística)
Se trata de reseña de Fernández Pérez, M. (1999), Introducción a la Lingüística, Barcelona, Ariel.